Understanding the Impact on Learners' Reading Performance and Behaviour of Matching E-Learning Material to Dyslexia Type and Reading Skill Level - Alghabban, Weam Gaoud; Al-Dawsari, Hadeel Mohammed; Hendley, Robert (HCI in Games: Serious and Immersive Games, 2021)
Dyslexia is a universal reading difficulty where each individual with dyslexia can have a different combination of underlying reading difficulties. For instance, errors in letter identification or omissions or transpositions within or between words. Nowadays, adaptive e-learning and gamification have become more common. Different learner characteristics have been used when adapting e-learning systems, such as the user’s learning style or knowledge level. However, little attention has been directed towards understanding the benefits of using dyslexia type or reading skill level when adapting systems for learners with dyslexia. This, despite dyslexia type and reading skill level being significant factors in their education and learning. This paper reports on research which aims to improve this understanding through empirical studies designed to evaluate the benefits of adaptation with native Arabic speaking children with dyslexia. A mixed-methods approach was used. In the first experiment the focus is on a qualitative understanding of the effects of adaptation based on dyslexia type. The second experiment provides a quantitative analysis of the effects of adaptation based upon the reading skill level of learners with dyslexia. Findings revealed that the majority of learners are motivated when adapting learning material to dyslexia type. Analysis of the results indicated that adapting based on reading skill level does achieve improved learning gain and lead to greater learner satisfaction compared to a non-adaptive version. Implications of these experiments are discussed.